Detailed Histologic Evaluation of Eosinophilic Esophagitis in Pediatric Patients Presenting with Dysphagia or Abdominal Pain and Comparison of the Histology between the Two Groups - Thirumazhisai S. Gunasekaran; Christopher Chu; Nemencio Ronquillo; Rohini Chennuri; Brian Adley; Kristina Borgen; Alan Schwartz; Robert Newberry; James Berman (Canadian Journal of Gastroenterology and Hepatology)
EoE in children presents with four main symptoms. Most common symptoms exhibited by our clinic population are dysphagia (D) and abdominal pain (AP). Despite similar treatments, we found in an earlier study that the outcomes between these two groups were different. Therefore, we investigated if there exist any histological differences between these groups that could further our knowledge of EoE. Aim. To compare esophageal histology in detail, apart from the eosinophil count, between EoE-D and EoE-AP. Method. Biopsies of patients with EoE-D and EoE-AP were reevaluated for 10 additional histological criteria, in addition to the eosinophil count. Results. Both groups had 67 patients; peak mean eosinophil was 33.9 and 31.55 for EoE-D and EoE-AP (p<0.05). Eosinophilic microabscesses, superficial layering of eosinophils, and epithelial desquamation were twice as common and significant in EoE-D group than EoE-AP. Eosinophil distribution around rete pegs was also significantly higher in EoE-D group. The remaining criteria were numerically higher in EoE-D, but not significant, with the exception of rete peg elongation. Conclusion. EoE-D patients have significantly higher eosinophils compared to EoE-AP, and the level of inflammation as seen from eosinophil microabscesses, superficial layering, desquamation, and the distribution around rete pegs is significantly higher.